2015
DOI: 10.1371/journal.pone.0120405
|View full text |Cite
|
Sign up to set email alerts
|

Depsides: Lichen Metabolites Active against Hepatitis C Virus

Abstract: A thorough phytochemical study of Stereocaulon evolutum was conducted, for the isolation of structurally related atranorin derivatives. Indeed, pilot experiments suggested that atranorin (1), the main metabolite of this lichen, would interfere with the lifecycle of hepatitis C virus (HCV). Eight compounds, including one reported for the first time (2), were isolated and characterized. Two analogs (5, 6) were also synthesized, to enlarge the panel of atranorin-related structures. Most of these compounds were ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 36 publications
0
30
0
1
Order By: Relevance
“…We also observed the protease-inhibitory effect of NSC87511 ( Supplementary Table 1) during the FIPV 3CL pro inhibition assay. Stictic acid derivatives and atranorin that were extracted from lichens using acetone could inhibit the replication of hepatitis C virus (Vu et al, 2015). In addition, the stictic acid also exhibited anti-HIV-1 integrase activities, with IC 50 < 50 μM (Neamati et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…We also observed the protease-inhibitory effect of NSC87511 ( Supplementary Table 1) during the FIPV 3CL pro inhibition assay. Stictic acid derivatives and atranorin that were extracted from lichens using acetone could inhibit the replication of hepatitis C virus (Vu et al, 2015). In addition, the stictic acid also exhibited anti-HIV-1 integrase activities, with IC 50 < 50 μM (Neamati et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…The five known compounds atranorin (1, 6.2 g), atranol (2, 10 mg), lobaric acid (3, 1.2 g), ursolic acid (4, 9.0 mg) and methyl 3'-methyllecanorate (5, 21 mg) were identified by direct comparison of their physical and spectral data in the literature [6,7]. Although the compounds have previously been described in some others species of genus Stereocaulon [4], here, they were reported for the first time in Stereocaulon evolutum (figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…Ranković et al [11] documented the potent antibacterial activity of ATR against the most dangerous respiratory tract bacteria, Staphylococcus aureus, comparable to streptomycin. Moreover, Vu et al [12] revealed that ATR possesses antiviral activity against the hepatitis C virus (HCV) with an IC 50 value equal to 22.3 ± 8.0 µM. ATR also reportedly possesses antimalarial activity toward the chloroquine-resistant W-2 and the CAM10 and SHF4 Plasmodium falciparum isolates [13,14].…”
Section: Introductionmentioning
confidence: 99%